Just kidding! : A to Z designs for kids & kidults. (Hong Kong : Viction:ary, 2013)
Toys and sweets are just not enough for our children today. With an insatiable appetite for new things, children are eager to explore and learn. They are the most open-minded and spontaneous audience, who are at all times building and living in a world of their own imagination. These young customers rely on their instincts, not patience, to judge and pick what they love and hate. Victionary's new title Just Kidding studies how contemporary product, environmental, and graphic designs for children draw on bold characters and decisions to inspire and appeal. The title presents today's most serious designs that not only look endearing, but are also creative, instructional, useful, and safe for children to play and interact with.
boek